The student as a client and their voice of complaint in digital spaces: a systematic review (2010–2024) (National Administration Journal, 2025)
The concept of the student as a client has been a topic of interest for many authors; however, the exploration of their complaint behavior in digital media related to educational services remains unclear. Understanding this issue will allow educational institutions to better address the needs of students who fit this profile. With this objective, the present article conducted a systematic literature review between 2010 and 2024 using Scopus and Google Scholar. The results revealed that studies on the topic exist, but in a fragmented manner. That is, there are various studies on the student-as-client concept, on student complaint or dissatisfaction behaviors, and on the use of digital channels by university students; however, no research has integrated these topics as a whole. In this sense, this article aims to present the most relevant and up-to-date information on the issue, in order to encourage the development of comprehensive studies and critical analysis on the subject.
Keywords: Student as client; educational services; digital media; networks; dissatisfaction; complaint behavior